2017
DOI: 10.4172/2229-8711.1000218
|View full text |Cite
|
Sign up to set email alerts
|

Woody Species Diversity of Parkland Agroforestry in Ethiopia

Abstract: Parkland agroforestry system has a crucial role in social, economic and environmental value. For instance, woody tree in Parkland improve soil fertility and enhancing crop productivity. Parkland tree have a potential of AM colonization and increase soil moisture to facilitate microbial activity. Park land agroforestry is a system where farm crops are mixed with trees to supply fodder, fuel, leaf litter, medicinal herbs, fruit, timber, etc. Predictably, the farmers have only grown a single crop on one field. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 4 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…An example is epibatidine, a chemical from the skin of the Phantasmal poison frog (Epipedobates tricolor). A derivative from this chemical has the ability to kill pain 200 times more effective than morphine, without the negative side effects [1]. Also, animals serve as medicinal tools, student specimens or are used to test new drugs [2].…”
Section: Medicinal Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…An example is epibatidine, a chemical from the skin of the Phantasmal poison frog (Epipedobates tricolor). A derivative from this chemical has the ability to kill pain 200 times more effective than morphine, without the negative side effects [1]. Also, animals serve as medicinal tools, student specimens or are used to test new drugs [2].…”
Section: Medicinal Resourcesmentioning
confidence: 99%
“…Among 45 islands 19 have churches and/or monasteries that are home for monks and other service providers to the churches and monasteries. Although biodiversity conservation may benefit not only the local communities but also the whole humanity, the costs are usually imposed to the local communities who depend on the natural resources or different goods and services [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the innovative solutions whose approach ensures higher productivity without further damaging natural resources base and allow adaptation to the changing climatic conditions world. Combining trees and crops in agroforestry systems improves the efficiency of utilization of resources (water, nutrient and light) and thus leads to an overall higher biomass production [19] . Simultaneously, it reduces soil erosion and nutrients leaching and landscape biodiversity increment [20] .…”
Section: Introductionmentioning
confidence: 99%
“…50-80% diversity, which is comparable to natural forest and also indicated that converting coffee and cocoa agroforestry systems to plantation reduced species richness by 46%, while conversion of natural forest to agroforestry resulted in merely an 11% reduction in species richness, farmers have a tradition of keeping valuable tree species and their farms act as refugees [18] . At the landscape level, agroforestry provides habitats that are suitable for a large number of native fauna and refuges biodiversity including ants, bats, frogs, lizards, bees, beetles and birds [17,19] . There are considerable differences in species richness between different agroforestry practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation